IL-10 Treatment Is Associated with Prohibitin Expression in the Crohn’s Disease Intestinal Fibrosis Mouse Model - C. Yuan; W.-X. Chen; J.-S. Zhu; N.-W. Chen; Y.-M. Lu; Y.-X. Ou; H.-Q. Chen (Mediators of Inflammation)
Prohibitin, which can inhibit oxidative stress and mitochondrial dysfunction, has been shown to have significant anti-inflammatory activities. Here, we investigate the effects of altering prohibitin levels in affected tissues in the interleukin-10 knockout (IL-10KO) mouse model with intestinal fibrosis. The aim of this study is to investigate the effects of IL-10 on prohibitin and the role of prohibitin in intestinal fibrosis of murine colitis. After the mice were treated with IL-10, prohibitin expression and localization were evaluated in IL-10KO and wild-type (WT, 129/SvEv) mice. The colon tissue was then investigated and the potential pathogenic molecular mechanisms were further studied. Fluorescence-based quantitative polymerase chain reaction (FQ-PCR) and immunohistochemistry assays revealed a significant upregulation of prohibitin with IL-10 treatment. Furthermore, IL-10 decreases inflammatory cytokines and TGF-β1 in the IL-10KO model of Crohn’s disease and demonstrates a promising trend in decreasing tissue fibrosis. In conclusion, we hypothesize that IL-10 treatment is associated with increased prohibitin and would decrease inflammation and fibrosis in an animal model of Crohn’s disease. Interestingly, prohibitin may be a potential target for intestinal fibrosis associated with inflammatory bowel disease (IBD).